ETIKA MEDIA MASSA ERA GLOBAL - Silvia Riskha Fabriar (An-Nida : Jurnal Komunikasi Islam, 2014)
Abstract The mass media was a means of delivering information simultaneously and could be accessed by the public at large. As a means of fulfilling people??s right to information, media should have rules as standardizations and commitments in accordance with the values and norms. The mass media had a lot of influence in the daily life today. Audiences were highly correlated and depended on the media that was consumed by a lot of people. Many of the issues were raised and packaged in such a way by the media to create new things. Thus, ethics became an important thing to keep the media and media actors were on the right track. Self-control of media actors through the existing ethics would be more solid if it was based on religious teachings. The Qur??an discussed each issue in all aspects of life, one of them was about how perceived the concept of mass media ethics. Keyword: media, ethics, global era, the Islamic perspective Media massa merupakan sarana penyampaian informasi secara serentak dan dapat diakses masyarakat secara luas. Sebagai sarana pemenuhan hak masyarakat atas informasi, media massa harus memiliki aturan sebagai standarisasi dan komitmen sesuai dengan nilai dan norma yang berlaku. Media massa memiliki banyak pengaruh di dalam kehidupan saat ini. Khalayak sangat berhubungan dan bergantung terhadap media yang dikonsumsi orang banyak. Banyak hal yang diangkat dan dikemas sedemikian rupa oleh media untuk menciptakan hal-hal baru. Dengan demikian, etika menjadi satu hal penting untuk menjaga media massa dan para pelaku media berada dalam jalur yang benar dan semestinya. Kontrol diri insan media melalui etika yang ada akan lebih mantap apabila dilandasi dengan ajaran agama. Al-Qur??an membahas setiap masalah dalam segala aspek kehidupan, salah satunya tentang bagaimana memandang konsep etika media massa. Keyword: Media massa, etika, era global, perspektif Islam